2013
DOI: 10.1063/1.4820358
|View full text |Cite
|
Sign up to set email alerts
|

Phase changes of filled ice Ih methane hydrate under low temperature and high pressure

Abstract: Low-temperature and high-pressure experiments were performed with filled ice Ih structure of methane hydrate under 2.0-77.0 GPa and 30-300 K using diamond anvil cells and a helium-refrigeration cryostat. In situ X-ray diffractometry revealed distinct changes in the compressibility of the axial ratios of the host framework with pressure. Raman spectroscopy showed a split in the C-H vibration modes of the guest methane molecules, which was previously explained by the orientational ordering of the guest molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 28 publications
11
27
1
Order By: Relevance
“…While our low-pressure data are in excellent agreement with previous authors, 14,19,21 we observed a different behaviour above 15-20 GPa. Specifically, both peaks progressively broaden with pressure (see Figure 1, right panel); however, we detected no splitting of either the ν 1 or ν 3 modes in the range 15-20 GPa or beyond; details of this frequency range are plotted in Figure 3 and compared with our simulation data.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…While our low-pressure data are in excellent agreement with previous authors, 14,19,21 we observed a different behaviour above 15-20 GPa. Specifically, both peaks progressively broaden with pressure (see Figure 1, right panel); however, we detected no splitting of either the ν 1 or ν 3 modes in the range 15-20 GPa or beyond; details of this frequency range are plotted in Figure 3 and compared with our simulation data.…”
Section: Resultssupporting
confidence: 92%
“…8 Therefore, several experimental studies in the last years focused on the high-pressure behavior of methane hydrates. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] As pressure increases beyond the kbar range, typically above 1-2 GPa, most ice clathrates undergo profound structural changes: the cages shrink and reorganize into structures bearing some ressemblance to ice phases, known as filled ices, 9 where the guest molecules occupy interstices in the ice lattices. 10 In filled ices, three different structures have been observed so far, and more recently a new "chiral hydrate" was established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for these discoveries is based on Raman spectroscopy carried out in a diamond anvil cell and supported by high-level computational calculations. Schaack et al (8) also show that their proposed structure for MH-IV is consistent with previously unresolved X-ray diffraction data reported by Tanaka et al (12). The mechanism of the MH-III to MH-IV phase transition is quite subtle and requires the reorganization of only a few hydrogen bonds, which explains why the H 2 O:CH 4 ratio can remain constant at 2:1 during the phase transition.…”
supporting
confidence: 75%
“…Recent studies also suggested that under high-pressure conditions methane and water could form stoichiometric mixed molecular crystals beyond the known MH-III phase: The existence of a new high-pressure phase in methane hydrate at pressures beyond 40 to 50 GPa was first hinted by Hirai and coworkers (1316), who observed a slow transition from MH-III into a different, yet unsolved structure during synchrotron X-ray diffraction experiments. The high-pressure structure was observed to survive up to 86 GPa, but the diffraction patterns did not allow the authors to identify it in detail.…”
mentioning
confidence: 99%